Quality assessment of cattle milk in Adea Berga and Ejerie Districts of West Shoa Zone, Ethiopia - Haile, S. (Haramaya University, 2015)
The objective of the study was to assess the hygienic handling practices, microbial as well as chemical composition of fluid milk in Adea Berga and Ejerie districts. A total of 180 smallholder producers, two dairy cooperatives, one dairy cooperative union, two milk processors and ten consumers were interviewed to collect the required information using a semi-structured questionnaire and focused group discussions. Survey works includes: Barn type and cleaning practices, hygienic condition of the milker and cows during milking, source of water used for cleaning purpose (udder, milker and milk utensils), type of milking container, fluid milk quality test methods, marketing system and major milk quality constraints. Preliminary quality tests and laboratory analysis were carried out to determine the PH level, Microbial quality and chemical composition. A total of 90 milk samples were collected and analyzed. About 32.2% of milk samples were checked with alcohol test positive; while 18.8% of the samples were positive to clot-on-boiling test. The specific gravity of milk samples were in the range of 1.024 to 1.032 in Ejerie district and 1.022 to 1.031 in Adea Berga district. The normal Specific gravity of milk ranges from 1.026 to 1.032. The overall mean value of fat, protein and Total solid (TS) were 3.52, 3.09 and 12.19, respectively. Fat percent was significantly different (P<0.05) among different source of sampling points. The highest milk fat content value was recorded at Adea Berga district (3.94). Overall mean total bacterial counts and coliform counts were 6.98±0.17, 4.84±0.10 log cfu/ml and significantly different b/n sites (P<0.05). The highest coliform (6.64 cfu/ml) and total bacteria counts (10.69 cfu/ml) were observed at consumers level. In general the result indicated that milk samples collected from smallholder milk producers, dairy cooperatives, dairy cooperative union, milk processor and consumers were subjected to microbial contamination and does not meet the international milk quality standard. Therefore, adequate sanitary measures should be taken at all stages from production to consumer level.